IDENTIFICATION OF KAZAKH HORSES BY MICROSATELITE DNA USING MODERN ANALYTICAL METHODS - Kargaeyeva Makpal; Baimukanov Dastanbek Asylbekovich; Nurbayev Serik Doldashevich; Baimukanov Aidar Dastanbekouly; Alikhanov Oralbek; Yusupbayev Zhaxylyk (Scientific Journal of Pedagogy and Economics, 2020)
Results of population and genetic structure on 17 microsatellite (MS) DNA loci of horses of the Aday breed bred in the Republic of Kazakhstan are presented. The number of the general population (samples) was 33 animals. Modern Kazakhstan population of the Kazakh horses of the Aday offspring is characterized by the following population and genetic indicators: an average number of alleles (N) –7.17, the average heterozygosity (expected He) –0.8226, average heterozygosity (expected, Ho) – 0.9180, the individual index of fixing (Fis) – 0.1171. 122 alleles were identified, of them 122 informative alleles (with a frequency more than 0.01), private - 0 (with a frequency less than 0.01) and effective - 99.29.